Prayer module for youth leaders - Laxa, James B. (Animo Repository, 2009)
This module is a prayer experience by itself. It intends to model to the participants one possible way of organizing a creative prayer experience that is sensitive to young people's prediction for visuals, sounds and yes, even taste. It tries to utilize symbols and symbolic actions that would provide an enriching spiritual experience.